2021
DOI: 10.33003/fjs-2021-0501-582
|View full text |Cite
|
Sign up to set email alerts
|

PROPERTIES OF ALUMINIUM/ELECTROLESS Ni-COATED SiC COMPOSITES - A REVIEW

Abstract: The combination of properties of Al/SiC composites make them very attractive materials for applications in automotive and aerospace industries. Several techniques are used in developing Al/SiC composites but stir casting process is most commonly used because it is the simplest and cost effective technique. However, composites produced via stir casting suffer from limitations such as low wettability and inadequate bonding between the molten Al & SiC particulates and the formation of degrading interfacial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Basically, oxidation can be defined as a reaction of metal and oxygen [2] but not limited to metal. In this study, the measured SiCp was heated in an Electrical Resistance Heating Furnace (Model: XD -1700M, manufactured by Zhengzhou Brother Furnace Co. LTD) already set to a temperature of 1300 o C required for the surface oxidation to take place, where a thin layer of SiO2 was formed on its surface.…”
Section: Treatment and Surface Oxidation Of Sicpmentioning
confidence: 99%
See 3 more Smart Citations
“…Basically, oxidation can be defined as a reaction of metal and oxygen [2] but not limited to metal. In this study, the measured SiCp was heated in an Electrical Resistance Heating Furnace (Model: XD -1700M, manufactured by Zhengzhou Brother Furnace Co. LTD) already set to a temperature of 1300 o C required for the surface oxidation to take place, where a thin layer of SiO2 was formed on its surface.…”
Section: Treatment and Surface Oxidation Of Sicpmentioning
confidence: 99%
“…The fabrication of composite materials is meant to produce materials with enhanced performances compared to its matrix alloy. It is observed that aluminium alloys are primary material of consideration for structural application but owning to their low strength behaviors, they are unsuccessful in service to meet the ever-increasing demands for high structural application performances [1][2][3][4]. Hence, ceramic particles like SiCp are used as reinforcement to strengthening the aluminium alloys to meet high structural applications [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1: Industrial usage of reinforcement materials (Odiwo et al, 2021) Many techniques are available for the fabrication of aluminium/silicon carbide particulate composites such as spray deposition, powder metallurgy, infiltration technique, squeeze casting and stir casting. However, stir casting is one of the most commonly used method to fabricate aluminium matrix composites because of its simplicity, ease of production of complex casting, mass production possibility and it is economical (Ramesh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%